2023
DOI: 10.1057/s41599-023-02304-7
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Intelligence in studies—use of ChatGPT and AI-based tools among students in Germany

Jörg von Garrel,
Jana Mayer

Abstract: AI-based tools such as ChatGPT and GPT-4 are currently changing the university landscape and in many places, the consequences for future forms of teaching and examination are already being discussed. In order to create an empirical basis for this, a nationwide survey of students was carried out in order to analyse the use and possible characteristics of AI-based tools that are important to students. The aim of the quantitative study is to be able to draw conclusions about how students use such AI tools. A tota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(9 citation statements)
references
References 22 publications
0
4
1
Order By: Relevance
“…The rather high percentage of positive statements ("4-I agree" and "5-I totally agree") of participants in our study regarding the individual items of the Intention to Use assessment scale (see the Appendix A), which was in the range from 75% to 79%, slightly exceeds the findings of a large-scale survey that was performed among college students in Germany [15] in May and June 2023, in which 63.2% of the respondents reported using ChatGPT or other AI tools. The data analysis regarding the correlation between usability and user experience variables, on the one side, and Intention to Use Bing Chat, on the other, revealed that the highest correlations (Pearson; statistically significant at p < 0.001) were obtained for Trust (r = 0.55), Perceived Usefulness (r = 0.42), Personification (r = 0.40), Cognitive Involvement (r = 0.37), Design Appeal (r = 0.37), Information Quality (r = 0.35), Risk Perception (r = 0.34), and Information Display (r = 0.33), respectively, on the one side, and Intention to Use Bing Chat on the other.…”
Section: Regression Analysis Of the Predictors Of The Intention To Us...contrasting
confidence: 82%
See 1 more Smart Citation
“…The rather high percentage of positive statements ("4-I agree" and "5-I totally agree") of participants in our study regarding the individual items of the Intention to Use assessment scale (see the Appendix A), which was in the range from 75% to 79%, slightly exceeds the findings of a large-scale survey that was performed among college students in Germany [15] in May and June 2023, in which 63.2% of the respondents reported using ChatGPT or other AI tools. The data analysis regarding the correlation between usability and user experience variables, on the one side, and Intention to Use Bing Chat, on the other, revealed that the highest correlations (Pearson; statistically significant at p < 0.001) were obtained for Trust (r = 0.55), Perceived Usefulness (r = 0.42), Personification (r = 0.40), Cognitive Involvement (r = 0.37), Design Appeal (r = 0.37), Information Quality (r = 0.35), Risk Perception (r = 0.34), and Information Display (r = 0.33), respectively, on the one side, and Intention to Use Bing Chat on the other.…”
Section: Regression Analysis Of the Predictors Of The Intention To Us...contrasting
confidence: 82%
“…Another Pew Research Center survey [14], performed in the period from 26 September to 23 October 2023, revealed that 13% of teens aged 13-17 (N = 1453) had used ChatGPT for their schoolwork. The fact that a much larger adoption rate is to be expected in higher education was revealed by a large-scale survey performed among college students in Germany [15] from 15 May to 5 June 2023 (N = 6311 in the final sample). In this study, 63.2% of the students reported that they had used ChatGPT or other AI tools, but still, only 34.8% of them had used such tools "occasionally", "frequently", or "very often".…”
Section: Introductionmentioning
confidence: 99%
“…This research endeavor is necessary to guide the ethical, responsible, and productive use of AI to enhance higher education guided by a robust scientific evidence [14,16,17]. The relevance of the quest to meticulously examine the benefits and challenges of AI in higher education is also important in light of the current evidence showing that a substantial number of university students are already using AI chatbots [18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…The ascend of ChatGPT has certainly intensified this debate, with worries about the new technology from scientists, educators and even students (see for example (3)). Indeed, recent survey evidence has shown that two thirds of students use ChatGPT in their studies (4). In this context, this paper seeks to test the effect of the continuous usage of ChatGPT on innovation, effort levels, and risk-behaviour among university students.…”
Section: Introductionmentioning
confidence: 99%